Hábito alimentar e percepção ambiental : um estudo de caso com estudantes do Ensino Médio em Natal-RN - Marinho, Augusto Santos (2006)
This study has as objective to examine the level of perception of high school students from two private schools in Natal-RN about the existence of a direct link between alimentary habit and its effects on environmental. The research was lead with 433 students, who had their school alimentary habits investigated according to the 24-hour recall method and presents the results of data collection from their opinions on participating in the generation of industrialized solid residues and their yearnings about the improvements of the standard of the food offered in the school. The students show a high rate of grading age for level at school, traditional family structure, riding, predominantly, by car or by bus in the house-school-house way, have generally all three important meals at home, feed frequently at their school, getting it from their won school, which included, mainly, soft drinks and fried or grilled appetizers; show a good knowledge about selective collectors, however with a high variation in their correct use. They show significant approval in the existence of a connection between their alimentary habits and debased effects about environmental and consider their food compounds at school could improve the offering of health/natural food, slowing industrialized foods, which are highly used, sometimes. The study on the students knowledge and concern level with regard to the interface alimentary habit-environmental impact allowed delimitating some of the mainly involved components in the alimentary choices of the same students in the school environment, what might help to develop a set of proposals that stimulates the formation of a responsible consumption standard among teenagers and the need of a consideration about the consequences of their choices